2020
DOI: 10.1021/acs.iecr.0c01562
|View full text |Cite
|
Sign up to set email alerts
|

Oxadiazole-Functionalized Fibers for Selective Adsorption of Hg2+

Abstract: Six kinds of 1,3,4-oxadiazole-functionalized fibers were prepared to evaluate the adsorption capacity for Hg 2+ . Finally, a functionalized fiber (PAN p-PMOD F) with the best adsorption performance was selected for further research. The PAN p-PMOD F fiber was characterized by infrared (IR), elemental analysis (EA), scanning electron microscopy (SEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The PAN p-PMOD F shows excellent selectivity for mercury ions in a mixed heavy metal ion solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For DHAQ, the survey spectrum (Figure S13a) shows that there exist C and O elements. And the C 1s peaks at 284.7, 285.9, and 287.2 eV belong to C–C/CC (carbons in anthraquinone ring), C–O, and CO bonds. , Peaks at 531.2 and 532.7 eV of O 1s correspond to CO and C–O bonds . As for DHAQ-PMO-10 (Figure S15), there exist C, N, O, and Si elements.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…For DHAQ, the survey spectrum (Figure S13a) shows that there exist C and O elements. And the C 1s peaks at 284.7, 285.9, and 287.2 eV belong to C–C/CC (carbons in anthraquinone ring), C–O, and CO bonds. , Peaks at 531.2 and 532.7 eV of O 1s correspond to CO and C–O bonds . As for DHAQ-PMO-10 (Figure S15), there exist C, N, O, and Si elements.…”
Section: Resultsmentioning
confidence: 71%
“… 58 , 59 Peaks at 531.2 and 532.7 eV of O 1s correspond to C=O and C–O bonds. 60 As for DHAQ-PMO-10 ( Figure S15 ), there exist C, N, O, and Si elements. The C 1s peaks at 283.8, 284.6, 285.4, 286.0, and 287.0 eV belong to C–Si, C–C/C=C (carbons in anthraquinone ring), C–N, C–O, and C=O bonds.…”
Section: Resultsmentioning
confidence: 93%
“…In detail, the decoloration process of BHET was more in line with the second model (R 2 > 0.990), which suggested that the adsorption process was dominated by chemiadsorption. 48 The value of H for decoloration increased rapidly with a higher temperature and then decreased slightly, which also reflected that the adsorption rate at higher temperature was significantly faster than that at lower one. The diffusion of the colorant into the pores of fresh D201 is of great significance.…”
Section: Resultsmentioning
confidence: 87%
“…Several isotherm equations are available to describe such curve shapes, one of which is the Temkin isotherm which has in recent years been used in an increasing number of articles reporting on water contaminant adsorption. Table presents a list of such papers published recently in Industrial & Engineering Chemistry Research . One observation that jumps out from Table is that the data fitting ability of the Temkin isotherm is often compared with those of the Langmuir and Freundlich isotherms. Although not as popular as the latter two isotherms, the Temkin isotherm is being used with sufficient frequency to merit wider awareness of its strengths and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In this research note, we revisit the Temkin isotherm to highlight some critical issues not frequently recognized by environmental adsorption researchers. 3 methylene blue DR, F, L, T Du et al 4 mercury F, L, T Xie et al 5 methylene blue DR, E, H, HJ, F, L, T Ouyang et al 6 arsenic F, L, T, RP Hao et al 7 cadmium DR, F, L, LF, RP, T Elmi et al 8 metribuzin DR, F, L, T Afshari et al 9 mercury F, L, T Guo et al 10 dyes F, L, T Zheng et al 11 chromium HL, L, T Trujillo et al 12 dyes F, L, T Sivalingam and Sen 13 arsenic DR, F, L, T Huang and Wang 14 lithium F, L, T Ge et al 15 A common form of the Temkin isotherm as used in environmental adsorption research can be written as eq 1, where q is the solid-phase concentration, c is the equilibrium liquid-phase concentration, R is the gas constant, T is the temperature, and b T and K T are adjustable parameters.…”
Section: Introductionmentioning
confidence: 99%